Riesgo laboral en turno nocturno relacionado al cancer de mama en enfermeras - Osorio-Calle, Yuli-Pilar (2022)
Objective: To identify the scientific evidence of occupational risk in night shift related to breast cancer in nurses. Methods: A review of the literature was carried out by consulting the following databases: PubMed, Science Direct, Scielo and Dialnet. Records were selected from 2012 to 2022, in Spanish, Portuguese and English on the topic of interest. Results: After critical reading analysis, a total of 16 studies were identified. Most studies report the occupational risk of the nurse is related to breast cancer with night shifts more than 3 per month, melatonin, exposure to artificial light during the night, circadian rhythm among others. Conclusions: Occupational risks are present, so the nurse in the face of increased risk of cancer should assume preventive-promotional self-care actions to promote their quality of life.